The Efektivitas Produk Pembiayaan Syariah BSI (Bank Syariah Indonesia) Terhadap Pemberdayaan UMKM : Bank Syariah - Rifqa Rosyita Ammaliah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
MSMEs are the backbone of the Indonesian economy, contributing significantly to GDP and employment. However, most businesses still face obstacles in accessing capital, making it difficult for them to grow and compete. Bank Syariah Indonesia (BSI) offers solutions through various sharia-based financing products such as mudharabah, musyarakah, murabahah, ijarah, and other schemes. This study aims to analyze the extent to which BSI's sharia financing products are effective in empowering MSMEs, in terms of increasing income, production capacity, and business sustainability. The method used is a literature review by examining various previous studies and secondary data sources related to sharia financing. The results of the analysis show that BSI's sharia financing is able to provide a significant positive impact, not only in the form of additional capital but also in the form of assistance, training, and strengthening of business networks. However, challenges remain, particularly the low level of sharia financial literacy among MSME players and the application procedures, which are considered quite complicated. Therefore, improving education and simplifying services is necessary so that Islamic financing can be more optimal in supporting the empowerment of MSMEs as the main drivers of the national economy.